2012
DOI: 10.5194/hess-16-967-2012
|View full text |Cite
|
Sign up to set email alerts
|

The Southern Annular Mode: a comparison of indices

Abstract: Abstract. The Southern Annular Mode (SAM) has been identified as a climate mechanism with potentially significant impacts on the Australian hydroclimate. However, despite the identification of relationships between SAM and Australia's hydroclimate using certain data sets, and focussed on certain time periods, the association has not been extensively explored and significant uncertainties remain. One reason for this is the existence of numerous indices, methods and data sets by which SAM has been approximated. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 53 publications
3
84
0
1
Order By: Relevance
“…This index is defined as the standardized mean sea level pressure differences between 408 and 658S, based on observations from 12 stations roughly distributed along these two latitudes. Several other SAM indices exist [see Ho et al (2012) for a review], some of which are based on principal component analysis of the pressuregeopotential height fields from global reanalyses, rather than latitudinal pressure differences. Following the conclusions from Ho et al (2012), we have elected to use the Marshall SAM index for its reliability prior to 1979 (when reanalyses are conversely less reliable) and thus for its temporal consistency throughout the time span of our reconstruction.…”
Section: E Sam Index and Sam-congruent Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…This index is defined as the standardized mean sea level pressure differences between 408 and 658S, based on observations from 12 stations roughly distributed along these two latitudes. Several other SAM indices exist [see Ho et al (2012) for a review], some of which are based on principal component analysis of the pressuregeopotential height fields from global reanalyses, rather than latitudinal pressure differences. Following the conclusions from Ho et al (2012), we have elected to use the Marshall SAM index for its reliability prior to 1979 (when reanalyses are conversely less reliable) and thus for its temporal consistency throughout the time span of our reconstruction.…”
Section: E Sam Index and Sam-congruent Trendsmentioning
confidence: 99%
“…Several other SAM indices exist [see Ho et al (2012) for a review], some of which are based on principal component analysis of the pressuregeopotential height fields from global reanalyses, rather than latitudinal pressure differences. Following the conclusions from Ho et al (2012), we have elected to use the Marshall SAM index for its reliability prior to 1979 (when reanalyses are conversely less reliable) and thus for its temporal consistency throughout the time span of our reconstruction. One must keep in mind, however, that this index emphasizes the zonally symmetric component of the SAM, whereas its asymmetric component, most prominent in austral winter and spring, is also known to have important climate impacts Fogt et al 2012).…”
Section: E Sam Index and Sam-congruent Trendsmentioning
confidence: 99%
“…While recent work has shown that these changes have been driven primarily by stratospheric ozone loss (Thompson and Solomon, 2002;Arblaster and Meehl, 2006;Thompson et al, 2011;Lee and Feldstein, 2013), it is also clear that the SAM has varied significantly over the past 140 years, likely in response to natural forcings (Jones et al, 2009). Differences among SAM indices have been discussed elsewhere (Jones et al, 2009;Ho et al, 2012), so we shall not do so here but rather treat them in aggregate, as they show very similar patterns of variability. We use a summer (DJF) measure of the SAM (Fig.…”
Section: Recent Circum-antarctic Circulation Changesmentioning
confidence: 99%
“…For example, during two of the three extended dry periods shown here the SAM is persistently positive. Note that while SAM is not shown to be positive during the Federation Drought (∼ 1895-1902) there is some question over the validity of the index used to represent SAM during the earlier part of the record (Ho et al, 2012); further, the influence of the SAM is very seasonally dependent for Australian rainfall (Hendon et al, 2007), with opposite effects on rainfall in summer versus winter, which may be negated when analyzing annual rainfall. As shown in Figure 6 the DMI was predominantly positive during the dry period that occurred between ∼ 1925-1945, contributing to the synchronicity observed during this period, particularly between Australia and South Africa.…”
Section: Synchronicity In Dry Spells Across the Southern Hemisphere Smentioning
confidence: 99%